The Beginnings, Means, and Ends of Interpretation in Yo también hablo de la rosa - Tremé, Matthew (Latin American Theatre Review, 2013)
This article explores how the formal dramatic structure of Emilio Carballido’s play conflates the dueling acts of artistic creation and critical interpretation. Whereas previous scholarship has primarily focused on the acts of interpretation that the play’s many characters carry out as they re-represent the actions of the protagonists that lead up to the climactic yet out-of-sequence train wreck, here the author examines why critics generally place the work’s first representation of these actions in a space of non-interpretation and the implications of subjecting that sequence of events to critical scrutiny. This analysis posits that interpretation here is not just a function of reception or re-telling; rather, it is embedded in the play’s structure, whose seeming transparency belies the web of manipulation that extends beneath its surface.